Inhibitory Member of the Apoptosis-stimulating Proteins of the p53 Family (iASPP) Interacts with Protein Phosphatase 1 via a Noncanonical Binding Motif - Llanos, Susana (American Society for Biochemistry and Molecular Biology, 2011)
Although kinase mutations have been identified in various human diseases, much less is known about protein phosphatases. Here, we show that all apoptosis-stimulating proteins of p53 (ASPP) family members can bind protein phosphatase 1 (PP1) via two distinct interacting motifs. ASPP2 interacts with PP1 through an RVXF PP1 binding motif, whereas the inhibitory member of the ASPP family (iASPP) interacts with PP1 via a noncanonical motif (RNYF) that is located within its Src homology 3 domain (SH3). Phe-815 is crucial in mediating iASPP/PP1 interaction, and iASPP(F815A) fails to inhibit the transcriptional and apoptotic function of p53. This study identifies iASPP as a new binding partner of PP1, interacting through a noncanonical PP1 binding motif.